A comparison of cognitive performance in the Suffolk County cohort and their unaffected siblings. (September 2021) - Valerio, Kate E.; Jonas, Katherine G.; Perlman, Greg; Bromet, Evelyn J.; Kotov, Roman
Highlights: Cases with SCZ and other psychoses both showed cognitive impairments. Cognitive impairment was more pronounced in those with SCZ than other psychoses. Siblings of SCZ cases showed deficits in processing speed and executive function. Siblings of cases with other psychoses showed no cognitive deficits. Case status explained 6.5 times as much variance in cognition as specific diagnosis. Abstract: People diagnosed with schizophrenia and other psychoses demonstrate impaired neuropsychological performance. Their unaffected siblings exhibit mild impairments relative to unrelated controls, suggesting genetic and shared environmental risk for psychosis account for some portion of cognitive impairments observed in cases. However, most sibling studies were conducted early in illness course. Studying cases and unaffected siblings later in life is valuable because diagnostic misclassification is common early in illness, possibly leading to spurious conclusions. This study compared neuropsychological performance of individuals with psychotic disorders (schizophrenia and other psychoses), their unaffected siblings, and controls. Assessments were conducted 20 years after case enrollment in the Suffolk County Mental Health Project, when siblings and controls were added to the protocol. Results showed individuals with schizophrenia and other psychoses performed worse than their matched siblings across domains. Relative to controls, siblings of participants with schizophrenia showed mild deficits in executive function and processing speed, while no significant differences were observed between siblings of those with other psychoses and controls. These findings suggest pre- and post-onset factors impact cognitive deficits in psychosis, but pre-onset factors are more salient in schizophrenia. Additionally, schizophrenia and other psychoses exist on a neurodevelopmental continuum, with schizophrenia being a more severe manifestation.